Knowledge and practices of Primary Care professionals on diabetic neuropathy: study of social representations - Erlon Gabriel Rego de Andrade; Ivaneide Leal Ataíde Rodrigues; Sidney de Assis da Serra Braga; Laura Maria Vidal Nogueira; Bruna Alessandra Costa e Silva Panarra; Marcandra Nogueira de Almeida Santos; Alexandre Aguiar Pereira (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze the knowledge and practices of Primary Health Care professionals about diabetic neuropathy through their social representations. Methods: a qualitative, descriptive study, anchored in the procedural aspect of the Theory of Social Representations. It was carried out in four Family Health Units in Belém-Pará, with 31 professionals from four health teams. Data were produced by individual semi-structured interviews, and the corpus was submitted to content analysis. Results: two thematic categories were defined, showing the participants' understanding and imagination about neuropathy, as well as the biopsychosocial repercussions of this complication in patients' daily lives. The multidisciplinary practices developed in the context of disease treatment/prevention and the consequences of this performance were also shown. Final Considerations: professionals' representations are anchored in neuropathy occurrence due to the deficient standard of care for themselves by patients, which results in the team's surpassing care attitude as an alternative to illness' challenges.